Design and Build an Information System for Credit Card and Unsecured Cards for Clients at Law Office Artha Tama - Puja Lestari; Sharyanto; Bernadus Gunawan Sudarsono (Journal of Engineering, Technology and Computing (JETCom), 2022)
Law Office Artha Tama is a law office company that is engaged in civil matters, especially negotiating services for discounts on repayment and rescheduling to various banks. Law Office Artha Tama is supported by partner lawyers and legal consultants who are able to work together professionally as a provider of legal services to parties who need them. Artha Tama's Law Office has been in existence for 5 years and its legality has been registered with the Ministry of Law and Human Rights of the Republic of Indonesia (Kemenkumham) since November 14, 2019. Likewise, when the settlement activity was carried out, it had not been stored properly because there was no direct activity record. connected with clients from the settlement department, this results in the absence of a complete report at the time of monitoring or evaluation of repayment. From the description of the problems that occurred, it designed and built a Web-based Client Credit Card and KTA Payment Information System at the Artha Tama Law Office which is expected to solve the existing problems. For the method of analysis and design, they used Unified Modeling Language (UML). The Web-Based Client Credit Card and KTA Repayment Information System at the Artha Tama Law Office uses the PHP and MySQL programming languages as the database. The method used in designing this information system is the System Development Life Cycle (DDLC) method.